2002
DOI: 10.1101/gad.962802
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of three regulatory serines of Tob by Erk1 and Erk2 is required for Ras-mediated cell proliferation and transformation

Abstract: tob is a member of an emerging family of genes with antiproliferative function. Tob is rapidly phosphorylated at Ser 152, Ser 154, and Ser 164 by Erk1 and Erk2 upon growth-factor stimulation. Oncogenic Ras-induced transformation and growth-factor-induced cell proliferation are efficiently suppressed by mutant Tob that carries alanines but not glutamates, mimicking phosphoserines, at these sites. Wild-type Tob inhibits cell growth when the three serine residues are not phosphorylated but is less inhibitory when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
157
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 47 publications
5
157
4
Order By: Relevance
“…Finally, it has already been shown that Tob1 can inhibit the classical pathway of CD28 costimulatory signaling [19]. Of note, the results of this study also demonstrate that human Th17 cells exhibit reduced levels of Skp2, which interacts with Tob1 and promotes its ubiquitin-dependent degradation [18]. Although the mechanisms responsible for the reduced Skp2 expression in Th17 cells remain presently unclear, this reduced expression may also contribute to the maintenance of high Tob1 levels in human Th17 cells.…”
mentioning
confidence: 52%
See 4 more Smart Citations
“…Finally, it has already been shown that Tob1 can inhibit the classical pathway of CD28 costimulatory signaling [19]. Of note, the results of this study also demonstrate that human Th17 cells exhibit reduced levels of Skp2, which interacts with Tob1 and promotes its ubiquitin-dependent degradation [18]. Although the mechanisms responsible for the reduced Skp2 expression in Th17 cells remain presently unclear, this reduced expression may also contribute to the maintenance of high Tob1 levels in human Th17 cells.…”
mentioning
confidence: 52%
“…In contrast, elimination of steady-state expression of Tob1 reduces the threshold of CD4 + T-cell activation required for optimal cellular proliferation and clonal expansion [19]. It seems that downregulation of Tob1 expression during cell-cycle entry is mediated at both mRNA and protein levels [18][19][20].…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations